2022
DOI: 10.1186/s13063-022-06826-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of whole brain radiation therapy for synchronous brain metastases with irradiation protecting the hippocampus versus whole brain radiotherapy for sequential brain metastases to boost irradiation in the treatment of brain metastases from SCLC: study protocol for a randomized controlled trial

Abstract: Background This study is in regard to the comparison of whole brain radiation therapy for synchronous brain metastases with irradiation protecting the hippocampus versus whole brain radiotherapy for sequential brain metastases to boost irradiation in the treatment of brain metastases from small cell lung cancer (SCLC). Therapeutically, they have notably varying dose distributions. Based on theoretical and model studies, it has long been speculated that these modes may result in different progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…When boosting lesions, conformal radiotherapy often cannot achieve ideal dose distribution, so techniques like xed-eld intensity-modulated radiotherapy (IMRT), volumetric modulated arc therapy (VMAT), and helical tomotherapy are generally chosen to achieve better dose conformation and homogeneity to the lesion while reducing irradiation doses to surrounding critical structures, thereby improving local control rates and reducing complications for patients. Preliminary studies have shown that VMAT has a dosimetric advantage in protecting the hippocampus during whole-brain radiotherapy and prophylactic cranial irradiation, but there are rare reports on hippocampal protection during boost irradiation following wholebrain radiotherapy both domestically and internationally [12][13][14][15]. Thus, in this study, we found that establishing a hippocampal protection zone can reduce the compression of cancer cells on the hippocampus with brain metastases from breast cancer.…”
Section: Discussionmentioning
confidence: 59%
“…When boosting lesions, conformal radiotherapy often cannot achieve ideal dose distribution, so techniques like xed-eld intensity-modulated radiotherapy (IMRT), volumetric modulated arc therapy (VMAT), and helical tomotherapy are generally chosen to achieve better dose conformation and homogeneity to the lesion while reducing irradiation doses to surrounding critical structures, thereby improving local control rates and reducing complications for patients. Preliminary studies have shown that VMAT has a dosimetric advantage in protecting the hippocampus during whole-brain radiotherapy and prophylactic cranial irradiation, but there are rare reports on hippocampal protection during boost irradiation following wholebrain radiotherapy both domestically and internationally [12][13][14][15]. Thus, in this study, we found that establishing a hippocampal protection zone can reduce the compression of cancer cells on the hippocampus with brain metastases from breast cancer.…”
Section: Discussionmentioning
confidence: 59%